Proceedings of the 8th International Conference on Pervasive Computing Technologies for Healthcare 2014
DOI: 10.4108/icst.pervasivehealth.2014.255179
|View full text |Cite
|
Sign up to set email alerts
|

User requirements for wearable smart textiles. Does the usage context matter (medical vs. sports)?

Abstract: Keywords 1. INTRODUCTION 1.1 Smart textiles 1.2 Technology acceptance -of new medical technologies perceived ease of use perceived usefulness attitude towards using technology actual system use voluntariness of use, output quality subjective norms social influence ease of use usefulness privacy trust security MAIN FOCUS OF THE STUDY AND QUESTIONS ADDRESSEDPermission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…27,63]. A few studies considered a combination of established acceptance models such as TAM and UTAUT in the domain of IS [59,64]. Due to the special context of FTs, researchers investigated the impact of social factors, as the usage of novel technologies can help individuals improve their image and differentiate them from other members of their peer group [6].…”
Section: Fitness Trackers and Technology Acceptancementioning
confidence: 99%
“…27,63]. A few studies considered a combination of established acceptance models such as TAM and UTAUT in the domain of IS [59,64]. Due to the special context of FTs, researchers investigated the impact of social factors, as the usage of novel technologies can help individuals improve their image and differentiate them from other members of their peer group [6].…”
Section: Fitness Trackers and Technology Acceptancementioning
confidence: 99%
“…In the case of Bpain, the device is extremely simple and intuitive, serving only one function and with limited user interaction, which results in high ease of use. This ease of use has been found to give the user a feeling of control over the device [53]. Regarding mobility, although cellphones are highly personal and usually close to their user, B-pain is a bracelet, so it can also be carried anywhere easily.…”
Section: Discussionmentioning
confidence: 99%
“…In preceding studies with both experts of smart interactive textiles as well as laypeople, ease of cleaning was perceived as an important criterion [ 25 , 28 ]. Thus, different levels of “ease of cleaning” are integrated in the current study: “usual cleaning”, “additional expense”, and “special cleaning”.…”
Section: Methodsmentioning
confidence: 99%
“…For example, van Heek et al contrasted product properties that relate to product acceptance of a smart shirt for recreational and medical use [ 25 ]. The study showed that the usage context influences the overall acceptance.…”
Section: Related Workmentioning
confidence: 99%